KAWIN HAMIL AKIBAT ZINA : Studi terhadap Persepsi Masyarakat Nagari Ranah Pantai Cermin, Solok Selatan - Zainal Azwar; Elfia Elfia (Turast: Jurnal Penelitian dan Pengabdian, 2021)
This study purpose to expose the perception of Pantai Cermin public towards the phenomenon of pregnant marriage due to adultery. This is caused by the increasing cases of pregnant marriages in Nagari Ranah Pantai Cermin from 2014 until 2017. The research questions are: What are the factors causing the increase of pregnant marriages due to adultery in Nagari Ranah Pantai Cermin, what are the public's opinions about pregnant marriages due to adultery, and what are the efforts done by the community to prevent pregnant marriages due to adultery. This research is a field research with a socio legal research approach. The collected datas were analyzed using qualitative methods. The research finds are: First, the factors that caused pregnant marriage in Nagari Ranah Pantai Cermin were the lack of parental supervision, promiscuity, weak sanctions, and misuse of technology. Second, The Public of Nagari Ranah Pantai Cermin assumpt that pregnant marriage is a very shameful act and in principle is not accepted by the public. However, the Society must accept it by perforce because they do not have the legitimate to punish the perpetrators. Eventually, the case of pregnant marriage became familiar to the public. Third, the efforts were done by the community to prevent pregnant marriages are increasing parental attention, obeying with regulations made by the local Society, carrying out sanctions that have been agreed upon by the religious leaders and ninik mamak, holding juvenile bonds, and sharing knowledge about the consequences of adultery.